Documenting and Describing from afar: the Amazigh of Eastern Nefusa Mountain - Flaviano, Mariacarmela (Libya-Italy: Shared Roots Future Visions, 2025)
Keywords: Berbérisme -- Djebel Nefousa

تمرد الامازيغية المضطهدة - قراده, إبراهيم (الحوار المتمدن, 2023)
Keywords: Berbérisme -- Djebel Nefousa

La politica berbera nella Libia coloniale: identità, reti e conflitti (1835-1924) - Pagano, Chiara (Studi Storici Carocci, 2025)
A seguito del crollo del regime di Gheddafi l’etnicità berbera/amazigh ha fornito un efficace dispositivo di affermazione politica ad alcuni gruppi libici che si sono mobilitati in aperta polemica con il paradigma panarabo dominante. L’attivismo amazigh ha ricercato nel passato gli argomenti per legittimarsi nel presente, riaffermando un legame originario con il territorio per rivendicare il riconoscimento come popolo indigeno, più che come minoranza. Eppure, come l’identità nazionale, anche l’identità etnica è un prodotto storico contingente, plasmato da specifici processi politici. Il volume ricostruisce in chiave critica la (ri)produzione dell’etnicità amazigh nella storia della Libia contemporanea, focalizzandosi sul periodo tra la metà dell’Ottocento e l’avvento del fascismo. Vengono così analizzate le rivendicazioni avanzate da attori locali definiti come “berberi” nei confronti delle autorità ottomane prima e coloniali poi. Da queste emerge come la politica berbera promossa dalle autorità italiane, e fatta propria da alcuni notabili tripolitani, individuò nell’etnicità uno strumento privilegiato per l’organizzazione gerarchica della società coloniale. Fu allora che vennero poste le basi delle dinamiche identitarie che, ancora oggi, naturalizzano l’opposizione tra gruppi arabi e berberi proiettandone le origini in un passato indefinito.
Keywords: Berbérisme -- Djebel Nefousa; Berbérisme -- Libye

مع احتفالاتهم بحلول رأس السنة الأمازيغية الجديدة.. ماذا تعرف عن "أمازيغ ليبيا"؟ (العربية, 2025)
Keywords: Berbérisme -- Djebel Nefousa

L’activisme berbère libyen en ligne et en diaspora, depuis le printemps berbère - Labaied, Sami (Material Culture, Identity, and the Construction of Amazigh Cultural Heritage, 2024)
Keywords: Berbérisme -- Djebel Nefousa; Vie politique -- Djebel Nefousa

The Role of Amazigh Libyan Civil Society in the Tamazgha Spring - Buzakhar, Madghis; Buzakhar, Mazigh; Buzakhar, Nasser (Studi Magrebini, 2016)
The fall of Gaddafi’s regime in 2011 has had a significant impact on the development and implementation of different social and political reforms in Libya. During the 1969-2010 period, the Libyan regime, its political system and national policies had been set against the Amazigh, who were thus unable to develop their own social and political organizations. Since the regime change, Libyan society has been drawn into political struggle, but has also had the chance to reorganize itself. There is no doubt that Amazigh civil society has played an essential role, emerging as a cultural and political player during the revolution on the upper hills of the Infusen (Nefusa) mountain range in 2011. Moreover, the movement progressed during the post-revolutionary period as a cultural and political advocate seeking reconsideration and recognition within the country’s constitutional framework. This paper highlights recent developments in Libya, the crucial role of the Amazigh civil society during the period of the revolution and its essential movement towards the uprising that toppled Colonel Gaddafi. The paper seeks to present the methods used to mobilize people with highly ambitious goals of social and political transformation. It presents some of the aspects of how Amazigh civil society managed to benefit from the media as a tool of promotion, developing political entities and outreach at a global scale in order to influence society and public opinion, through methods including advocacy, campaigning, building partnerships and developing social and political projects.
Keywords: Berbérisme -- Djebel Nefousa

Les Berbères du Jebel Nefousa dans la Libye d’après Kadhafi : une perspective historique - Morone, Antonio M.; Pagano, Chiara (États-nations contre minorités, 2023)
Durant le régime de Mouammar Kadhafi, qui a duré plus de quatre décennies, la minorité berbère en Libye a été systématiquement écartée de la politique, de l’histoire et de la mémoire de la Grande Jamahiriya arabe libyenne socialiste issue de la Révolution de 1969. L’unicité supposée et l’homogénéité de la nation libyenne, nivelée sur l’identité arabe et islamique sunnite, ne laissait pas d’espace à une quelconque revendication identitaire concurrente ou alternative. Pour le régime, la simple affirmation de l’existence d’une minorité berbère était automatiquement perçue comme une manifestation de dissidence politique et réprimée en conséquence. Il n’y a guère à s’étonner dès lors que, dans les interstices de la guerre civile, déclenchée par la révolte contre le régime de Mouammar Kadhafi en 2011, se soit progressivement affirmée la revendication de la protection des droits individuels et collectifs des Berbères. Les Berbères du Jebel Nefousa, qui est historiquement la troisième région la plus importante du pays pour la population résidente après Tripoli et Benghazi, ont joué un rôle moteur dans la cause des Berbères de Libye qui vivent aussi dans la ville côtière de Zouara et dans les oasis de Sawknah et Awjilah.
Keywords: Berbérisme -- Djebel Nefousa

Berber Majority Ibadhi Minority in North Africa : Ibadhi community in Libya (Nafousa), Tunisia (Djerba) and Algeria (Mzab) - Umādī, Mūḥammad (Ibadism, Ibadi Studies, and the Sultanate of Oman, 2009)
Keywords: Berbérisme -- Djebel Nefousa; Berbérisme -- Djerba; Berbérisme -- Mzab

Six ans avant, comment les berbères libyens préparaient la chute de Kadhafi (1) - Moreau, Aurélie (2013)
A l’étranger ou en Libye, les Berbères ont contribué à la victoire des forces révolutionnaires face à Kadhafi, durant la guerre civile libyenne. Sur le terrain d'abord, où ils ont mené plusieurs…
Keywords: Berbérisme -- Djebel Nefousa

Les ibadites du djebel Nafûsa après la révolution libyenne - Dbeez, Nabel (Horizons maghrébins, 2017)
Keywords: Berbérisme -- Djebel Nefousa

Due volte minoranza: i berberi ibaditi del jabal Nafusa nella visione coloniale - Cresti, Federico (Minoranze, pluralismo, stato nell'Africa mediterranea e nel Sahel, 2015)
Keywords: Berbérisme -- Djebel Nefousa

I Berberi nella Libia post-Gheddafi: il caso del Jebel Nefusa tra storia e presente - Morone, Antonio M.; Pagano, Chiara (Il Politico, 2015)
Keywords: Berbérisme -- Djebel Nefousa